2016
DOI: 10.1111/imj.13020
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anaemia and iron deficiency in Portugal: the EMPIRE study

Abstract: Anaemia and iron deficiency are highly prevalent in Portugal and largely undiagnosed. Women, young adults and older individuals are more prone to present these conditions and there are marked regional asymmetries. Nationwide strategies for prevention, diagnosis and treatment of these conditions should be implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 36 publications
7
45
2
1
Order By: Relevance
“…On the contrary, up to 37.3% and 32.1% of older adults in Dominican Republic and Puerto Rico were classified as having anemia, respectively [24]. The present results indicate that the prevalence of anemia in older Ecuadorians is comparable to that recently described among subjects aged 65 years and older in Portugal (21.0%) [25]. …”
Section: Discussionsupporting
confidence: 72%
“…On the contrary, up to 37.3% and 32.1% of older adults in Dominican Republic and Puerto Rico were classified as having anemia, respectively [24]. The present results indicate that the prevalence of anemia in older Ecuadorians is comparable to that recently described among subjects aged 65 years and older in Portugal (21.0%) [25]. …”
Section: Discussionsupporting
confidence: 72%
“…2 Iron deficiency is an important comorbidity factor in chronic heart failure (HF), as well as in HF decompensation periods, regardless of the presence of anemia. 1 , 3 …”
Section: Introductionmentioning
confidence: 99%
“…In 2002, worldwide prevalence of anemia, diagnosed according to the World Health Organization (WHO) criteria—hemoglobin <12 g/dL for females and <13 g/dL for males—was estimated to be around 25% in the general adult population and 24% in people over 60 years of age . Recent studies have reported that anemia is present in 6% to 22% of females and 8% to 20% of males above 65 years of age, in 29% of females and 34% of males above 80 years of age, reaching a higher prevalence of 41% to 66% in hospitalized elderly patients …”
Section: Introductionmentioning
confidence: 99%